Hubungan Literasi Gizi, Perilaku Jajan, dan Kecukupan Gizi dengan Status Gizi - Setyaningrum, Yahmi; Amaliyah, Rizky; Maulidiyah, Siva (Media Literasi Indonesia, 2025)
Elementary school-age children are ideally expected to make nutritious snack choices to support their growth and development. However, in reality, many still exhibit low nutrition literacy, unhealthy snacking behaviors, and inadequate nutrient intake, all of which may influence their nutritional status. This study aims to analyze the relationship between nutrition literacy, healthy snack selection behavior, and nutrient adequacy with the nutritional status of elementary school students. The study employed a correlational survey design with a cross-sectional approach. A total of 42 students were selected using probability random sampling. Data on nutrition literacy and snack selection behavior were collected using structured questionnaires that had been tested for validity and reliability. Nutrient adequacy was assessed using the SQ-FFQ, and nutritional status was measured using BMI-for-age indicators. Data analysis was conducted using cross-tabulation and Spearman Rank correlation tests. The results showed no significant relationship between nutrition literacy and nutritional status (p = 0.051), but there were significant associations between healthy snack selection behavior (p = 0.023) and nutrient adequacy (p = 0.000) with nutritional status. These findings suggest that actual dietary behavior and fulfillment of daily nutrient needs have a stronger influence on nutritional status than knowledge alone. Therefore, nutrition interventions for schoolchildren should focus not only on improving literacy but also on fostering sustainable healthy eating habits.